(untitled) (Research, Society and Development, 2021)
Physalis peruviana L. is a plant widely used in food for providing potential health benefits, associated with melhorias in physiological processes, which are related to the presence of important bioactive, such as phytosteróis, polyphenois and vitamins A and C and to be considered A natural functional food has been alve of scientific and commercial interest due to a variety of compost. Either this study seeks to carry out in a systematic way, or to raise scientific evidence that it is possible to use this plant not for cancer treatment. A review was compiled by original and experimental studies published in national and international journals, responding to the guiding question: What are the evidências available in literature about the potential of the Peruvian Physalis species for the treatment of cancer? The research results will show that Physalis peruviana L. in s-eus derivatives shows cytotoxic activities against various types of cancer cells, by different mechanisms and apoptotic pathways, such as activation of Caspases 9, 8 and 3, release of cytochrome C, activation of p53 protein and activation of Bax and Bcl-2, an important mechanism of anticancer activity, as well as seletivity demonstrated in some two studies, enabling or developing safer therapeutic alternatives.